The Association between Soy Food and Breast Cancer; a Multicenter Cross-Sectional Study at Taif City, Saudi Arabia - S., M.D, Alnefaie; K., Alqashqari; A., Almalki; A., Baabbad; A., Alrabie; N., Almalki (International Journal of Innovative Research in Medical Science, 2021)
Background: Breast cancer (BC) has a high incidence rate among females (3 to 8 per 1000) and is one of the most common causes of cancer-related death. Diet is considered one of the risk factors in BC. Phytoestrogens are chemical components similar to estrogen in structure. An isoflavone is a major group of phytoestrogens, and it is found in food like soy products. Aim: Our study investigates the association between soy food intake, BC development and mammogram density among women in Taif City, Saudi Arabia. Methods: A descriptive cross-sectional study was conducted in three hospitals in Taif City, Saudi Arabia. The data was gathered using a questionnaire created by the authors. Phone interviews were conducted with female patients who visited breast/general surgery clinics from January to July 2020. Results: A total of 194 patients participated in this study. We observed that only two female patients (1.03%) had a history of high soya intake, and both developed BC (p = 0.011). One-third (33.5%) showed scattered areas of fibro-glandular densities in a mammogram. Conclusion: We found that a large amount of soy food intake was significantly associated with a higher risk of BC. There is no relationship between mammogram density and age based on soya intake. More prospective studies with larger sample sizes in different cities of Saudi Arabia are needed to confirm this association.